Characterization of Escherichia coli isolated from cultured catfish by antibiotic resistance and RAPD analysis - Samuel, Lihan; Marian, M. M; Kasing, Apun; Lesley Maurice, Bilung; Son, Radu (IFRJ Publisher, 2011)
Antibiotic susceptibility and genetic diversity of E. coli isolated from cultured catfish and their surrounding environment were determined. The levels of resistance of the E. coli isolates towards six different antibiotics tested differed considerably. Though the isolates displayed resistance towards some of the antibiotics tested, none of the isolates showed resistant towards norfloxacin, sulphametoxazole/trimethoprim and chloramphenicol. RAPD-PCR analysis using single primer and primers combination clustered the E. coli isolates into 3 and 5 groups, respectively. The results of this study suggest that the E. coli isolates from the catfish and their surrounding environment derived from a mixture of sensitive and resistant strains with diverse genetic contents. The use of the RAPD analysis is sufficiently discriminatory for the typing of the E. coli isolates.